PENERAPAN MODEL PEMBELAJARAN (THINK PHAIR SHARE) TPS UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF MATERI BIOTEKNOLOGI - Salimah, Ika Nur (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
The study was conducted as a classroom action research, aimed at examining the academic performance of students in a science class who were provided with biotechnology materials. The results indicated that the learning outcomes of the students were suboptimal. The present investigation employs the Think Pair Share (TPS) learning framework. The study was conducted through two distinct research cycles, with each cycle encompassing planning, implementation, observation, and reflection stages. The educational institution in question is Nurul Fallah Middle School, located in the district of Banyuwangi. The present student population comprises 19 individuals, with a gender distribution of 12 males and 7 females. Data collection involved the utilization of written assessments to measure cognitive domains. Following each iteration of analysis, the research findings have exhibited enhancement, whereby the mean academic achievement of pupils prior to the implementation of the TPS pedagogical approach was 68, and the rate of completion was 53%. During the initial academic cycle, the mean academic grade attained by students was 73, and the percentage of students who successfully graduated was 74%. During the second cycle, the students attained an academic mean of 83 and a completion percentage of 95%. There was a 21% rise in percentage from period 1 to period 2. The findings indicate that implementing the TPS (Think Pair Share) instructional approach enhances the cognitive learning achievements of biotechnology topics among 9th-grade students at SMP Nurul Fallah Banyuwangi during the academic year of 2022/2023.